Impact of Transportation and Supply Chain of Manufacturing Industries: A Case Study of Sulfo Rwanda Industries (2016-2018) - Mbonimana Gamariel; Akayezu Marie Noella (Journal La Bisecoman, 2021)
This research analyzed the perceptions on impact of transportation on supply chain of manufacturing industries in Sulfo Rwanda, Kigali city. The purpose of the study is to know the effects of transportation on supply chain in manufacturing specially Sulfo. The study adopted the descriptive and correlation designs in order to get the understanding of the findings from the respondents who were the employees of sulfo and some customers. The population of this study was totalised 136 respondents. The sample size was 58. The findings demonstrated that there is a relationship between transportation and supply chain management. This is confirmed by a Pearson correlation of .970 between transportation and supply chain. Thus, the conclusion was that transportation have effects on supply chain management. The researcher recommended that SULFO management should continue to building a competitive infrastructure, leveraging worldwide logistics, synchronizing supply with demand and measuring performance globally, providing on having sufficient raw materials which are used in production, by finding others suppliers so that in case there is shortage of raw materials, others suppliers provide. Finally, Sulfo should manage production cost for getting high profit. It is suggested that the model can be used for shippers in negotiating service improvements with carriers and by carriers in negotiating service improvements with shippers.